CHALLENGES AND EXPECTATIONS FOR THE IMPLEMENTATION OF CUSTOMARY LAW (COMPARATORY ASPECTS OF INDONESIA AND OMAN) - febrianty, yenny; Handoyo, Sapto; Fitri, Hidayati; Hidaya, Wahab Aznul; Taranama P.M., Hilton (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Focusing on the connection between customary law and human rights concepts, this study seeks to examine the difficulties and potential solutions surrounding the recording, regulation, and application of customary law in Oman and Indonesia. This study compares and contrasts two nations, Oman and Indonesia, using a normative and comparative method. Literature reviews, statutory rules, official papers, and policies pertaining to law are all sources of legal information. According to the study's findings, the most significant problems include a lack of documentation of customary law, clashes between customary law and human rights principles, and difficulties in incorporating customary law into the country's legal system. A portion of the suggested remedy is to bring formal law and customary law into closer alignment, and another element is to increase indigenous people's involvement in the legislative and judicial processes.